Asymmetric floor heave mechanism and groove cutting pressure relief control technology in mining roadways - HUANG Yutong; ZANG Chuanwei; BAI Yongrui; ZHANG Fan (Gong-kuang zidonghua)
In mining roadways located between solid coal and small coal pillars, the problem of asymmetric floor heave is severe due to the influence of factors such as asymmetric support pressure, plastic deformation of small coal pillars, and weak floor strata. Traditional support technologies are difficult to effectively control this issue. To address this issue, a combination of theoretical analysis, numerical simulation, and field testing was employed to analyze the stress distribution characteristics and reveal the formation mechanism of asymmetric floor heave. A groove cutting pressure relief control technology was proposed, in which grooves of specific depth and width were cut into the roadway floor to transfer high shallow stress to the deep rock mass outside the pressure relief groove, while also providing deformation space for the shallow surrounding rock. This reduced stress concentration and the accumulation of deformation energy, thereby effectively suppressing floor heave. Theoretical calculations indicated that the maximum failure depth of the roadway floor was 2.04 m, and numerical simulations were used to determine the optimal parameters for field groove cutting. Industrial-scale field test results showed that the floor heave amount in the groove cutting pressure relief site was reduced by 94.99% compared to the non-grooved site, verifying that groove cutting pressure relief can effectively resolve the problem of floor heave in practice.